Body Odor Based Personality Judgments: The Effect of Fragranced Cosmetics - Sorokowska, Agnieszka; Sorokowski, Piotr; Havlíček, Jan (Frontiers in Psychology, 2016)
People can accurately assess various personality traits of others based on body odor alone. Previous studies have shown that correlations between odor ratings and self-assessed personality dimensions are evident for assessments of neuroticism and dominance. Here, we tested differences between assessments based on natural body odor alone, without the use of cosmetics and assessments based on the body odor of people who were allowed to use cosmetics following their daily routine. Sixty-seven female observers assessed samples of odors from 113 odor donors (each odor donor provided two samples – one with and one without cosmetic use); the donors provided their personality ratings, and the raters judged personality characteristics of the donors based on the provided odor samples. Correlations between observers’ ratings and self-rated neuroticism were stronger when raters assessed body odor in the natural body odor condition (natural BO condition; rs = .20) than in the cosmetics use condition (BO+cosmetics condition; rs = .15). Ratings of dominance significantly predicted self-assessed dominance in both conditions (rs = .34 for natural BO and rs = .21 for BO+cosmetics), whereas ratings of extraversion did not predict self-assessed extraversion in either condition. In addition, ratings of body odor attractiveness and pleasantness were significantly lower in natural BO condition than in BO+cosmetics condition, although the intensity of donors’ body odors was similar under both conditions. Our findings suggest that although olfaction seems to contribute to accurate first impression judgments of certain personality traits, cosmetic use can affect assessments of others based on body odor.